2016
DOI: 10.18632/oncotarget.9771
|View full text |Cite
|
Sign up to set email alerts
|

Folate-targeted star-shaped cationic copolymer co-delivering docetaxel and MMP-9 siRNA for nasopharyngeal carcinoma therapy

Abstract: The co-delivery of drug and gene has become the primary strategy in cancer therapy. Based on our previous work, to co-deliver docetaxel (DOC) and MMP-9 siRNA more efficiently for HNE-1 nasopharyngeal carcinoma therapy, a folate-modified star-shaped copolymer (FA-CD-PLLD) consisting of β-cyclodextrin (CD) and poly(L-lysine) dendron (PLLD) was synthesized, and then used for DOC and MMP-9 co-delivery. Different from commonly used amphiphilic copolymers micelles, the obtained CD derivative could be used directly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…In vivo assays showed that codelivery of docetaxel/MMP-9 siRNA inhibited HNE-1 tumor growth and decreased expression of the cell proliferation marker proliferating-cell nuclear antigen (PCNA), suggesting that it could be a promising strategy for treatment of localized tumors such as nasopharyngeal carcinoma. 318 …”
Section: Discussionmentioning
confidence: 99%
“…In vivo assays showed that codelivery of docetaxel/MMP-9 siRNA inhibited HNE-1 tumor growth and decreased expression of the cell proliferation marker proliferating-cell nuclear antigen (PCNA), suggesting that it could be a promising strategy for treatment of localized tumors such as nasopharyngeal carcinoma. 318 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, gene targeting therapy has come into the spotlight in team researches and clinical trials [19][20][21]. Our previous studies have, respectively, developed a cyclodextrin-poly derivative [22] and a folate-targeted cationic copolymer [23] to carry docetaxel and MMP siRNA plasmid for better anti-NPC treatment. In vitro assay demonstrated the superiority of the composites in promoting tumor cell apoptosis and inhibiting their invasion ability.…”
Section: Resultsmentioning
confidence: 99%
“…However, other researchers hold a different opinion and the causal mechanism of this imbalance remains unclear. In addition, in the past two years, an increasing number of studies have revealed the relationship between MMP-9 and oesophageal squamous cell carcinoma [ 34 ], ovarian cancer [ 35 ], nasopharyngeal carcinoma [ 36 , 37 ], Ewing sarcoma [ 38 ], and bladder cancer [ 39 ]. Different microenvironments and tissue interactive mechanisms may lead to the presence of the divergence.…”
Section: Discussionmentioning
confidence: 99%